A case of adrenocortical carcinoma accompanying secondary acute adrenal hypofunction postoperation - Kai Kou (World Journal of Surgical Oncology, 2018)
Abstract Background Adrenocortical carcinoma (ACC) is a rare, heterogeneous malignancy with a poor prognosis. ACCs are classified as functioning and non-functioning. The pathogenesis of ACC remains elusive, and diagnosis of ACC is currently based on pathology. In the absence of other effective approaches, surgical resection is the preferred treatment option. Case presentation Here, we report a case of ACC in the retroperitoneum. The patient underwent radical adrenalectomy and remained disease-free throughout a 6-month follow-up. Conclusions Radical surgical resection is an efficient therapy for ACC, and hydrocortisone can be used to alleviate symptoms of secondary acute adrenal hypofunction.